Prevalence of psychosocial dysfunctional behaviours among in-school adolescents in Ikere-Ekiti, Ekiti state, Nigeria (2018)
Psychosocial disorders affect people across all ages in both high and low income countries. Unfortunately, information on psychosocial functioning among children and adolescents are practically scarce in Nigeria. However, local studies can provide remote strategies to identify the risk factors, increase awareness, remove stigma and improve access to mental health services. In this work, prevalence of psychosocial disorders across participants’ demographic and background characteristics were examined.A self-administered Rosenberg Self-esteem Scale (RSS) and Strengths and Difficulties Questionnaire (SDQ) were used to screen for psychosocial symptoms among in-school adolescents. Participants were selected from six (6) secondary schools within Ikere Ekiti. The reliability of the scales were using Cronbach’s alpha. Preliminary data analyses were performed using descriptive statistics while independent t-test and ANOVA were used to compare psychosocial scores across selected background and demographic characteristics of the participants. The participants comprised 480 students, aged 11 to 19. Cronbach’s alpha showed a moderate reliability estimate of 0.60 for the SDQ and 0.43 for the RSS. It was observed that higher mean scores on self-esteem and prosocial behavior correlate with lower mean scores on psychosocial disorder symptoms. Moreover, male participants significantly (t=2.810, P=0.01) exhibited conduct problems more than their female counterparts while those from polygamous families also have higher inattention problems compared to their counterparts from monogamous homes (t= -2.980, p=0.003). The study revealed that boys are more exposed to externalizing behavioural problems while girls possess more pro-social features. Also, it was found that self-esteem and family type have an important role to play in adolescent psychosocial dysfunction.